2022
DOI: 10.3390/ma15238631
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Hybrid Manufacturing of AlSi5 Alloy Turbine Blade Prototype by Robotic Direct Energy Layered Deposition and Subsequent Milling: An Alternative to Selective Laser Melting?

Abstract: Additive technologies enable the flexible production through scalable layer-by-layer fabrication of simple to intricate geometries. The existing 3D-printing technologies that use powders are often slow with controlling parameters that are difficult to optimize, restricted product sizes, and are relatively expensive (in terms of feedstock and processing). This paper presents the development of an alternative approach consisting of a CAD/CAM + combined wire arc additive-manufacturing (WAAM) hybrid process utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The choice to use a descriptive research strategy in this investigation has been deliberate. The purpose of descriptive research is to paint a complete and accurate picture of the phenomenon being studied [16]. A descriptive research design is ideal for thoroughly investigating the current literature, mathematical models and machine learning techniques that are pertinent to EDM optimisation, given the purpose of merging these two approaches.…”
Section: Methodsmentioning
confidence: 99%
“…The choice to use a descriptive research strategy in this investigation has been deliberate. The purpose of descriptive research is to paint a complete and accurate picture of the phenomenon being studied [16]. A descriptive research design is ideal for thoroughly investigating the current literature, mathematical models and machine learning techniques that are pertinent to EDM optimisation, given the purpose of merging these two approaches.…”
Section: Methodsmentioning
confidence: 99%
“…J. Dugar et al in [32] have explored DED process for manufacturing a simple hollow blade and studied its mechanical properties. They also did a cost analysis comparing the DED solution with PBF and standard manufacturing processes.…”
Section: T Cokyasar Et Almentioning
confidence: 99%
“…They concluded that using HAM processes resulted in a high material yield and a better performance and flexibility than those of traditional forging methods. Dugar et al [76] used HAM, combining the WAAM in robotic machining to sustainably produce AiSi5 alloy turbine blades. They deduced that HAM enables an economically viable, resource/energy-feasible, and time-efficient production of complex parts.…”
Section: Hybrid Additive Manufacturing (Ham) Processesmentioning
confidence: 99%